THE EUROPEAN TEMPORARY PROTECTION DIRECTIVE AND THE UKRAINIAN REFUGEE CRISIS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The military conflict in Ukraine since the end of February 2022 has caused an unprecedented intra-European refugee crisis. More than 6 million Ukrainians left the country, and another 8 million were internally displaced. The policy of solidarity with the Ukrainian state faced the EU in exceptional circumstances and required a revision of the existing legislation in the field of international protection. The report offers a comparative analysis of the transposition practices of the Council Directive 2001/55/EC on minimum standards for the granting of temporary protection, activated for the first time since its adoption. The legislations of sixteen countries that have become the main receivers of the refugee flow have been examined, one of which is the Republic of Bulgaria.